__Steps to convert general form of Quadratic Function into completing the square form__**General form of quadratic function : $f(x)=a{x}^{2}+bx+c$**

Completing the square form : $f(x)=a{(x+p)}^{2}+q$

**: Make sure the coefficient ${x}^{2}$ is 1, if not factorize.**

*Step 1***: Insert $+{\left(\frac{coefficient\text{}\text{}-of\text{}x}{2}\right)}^{2}-{\left(\frac{coefficient\text{}\text{}-of\text{}x}{2}\right)}^{2}$**

*Step 2***: Completing the square [convert $f(x)=a{x}^{2}+bx+c$ into $f(x)=a{(x+p)}^{2}+q$ .]**

*Step 3*